WEBSITE PROMOSI KULINER DAN KERAJINAN KHAS PANDEGLANG - Kintan Mithardiyana Pratiwi (2020)
Culinary and craft from Pandeglang Regency are various kinds. However, information from culinary and craft doesn't have a container in the form of information systems. This is what makes it difficult for people to know about the culinary and craft of Pandeglang. Therefore, we need a container in the form of a special file directory that includes all culinary and craft information in Pandeglang Regency. The purpose of this research is to develop the Pandeglang Regency website by adding features that will later go to the Pandeglang Regency culinary and craft promotion page. In addition to displaying culinary and craft information, there is a sales information system that will benefit culinary and craft entrepreneurs. The research method uses the SDLC waterfall model which consists of 5 stages, namely communication, planning, modeling, construction, and deployment. With this website, this site can promote culinary and craft in Pandeglang and also can support the government program in Pandeglang Satu Data. The results of this research are web-based applications for the promotion of Pandeglang culinary and craft.